HASIL BELAJAR AKIDAH AKHLAK MELALUI PROBLEM BASED LEARNING BERBANTUAN GOOGLE CLASSROOM BERDASARKAN SIKAP TOLERANSI SISWA - Deden Hilmansah (STAI Ma'had Aly Al-Hikam Malang, 2023)
This study aims to analyze: 1) differences in learning outcomes of aqidah morals assisted by Google Classroom between students who study with problem-based learning models and students who study with active learning and conventional learning models in terms of student tolerance; and the effect of the interaction between the learning model and the attitude of tolerance on the learning outcomes of students' aqidah morals assisted by google classroom. This research is a quantitative research with a descriptive method. The data collection technique used is a test of the results of learning aqidah morals through Google Classroom and a student tolerance attitude questionnaire using a Likert scale. Data analysis in this study used a non-parametric statistical test, namely the median test. The results showed that; 1) there are significant differences in learning outcomes of aqidah morality assisted by Google Classroom between students who study with problem-based learning models and students who learn with active and conventional learning models; 2) there is a significant difference in learning outcomes of Aqidah Morals assisted by Google Classroom between students with high tolerance attitudes and students with moderate tolerance attitudes, this shows that tolerance attitudes have an influence on student Aqidah Morals learning outcomes where the higher the student's tolerance attitude, the learning outcomes moral aqidah will also increase, and vice versa; 3) the learning model factor and the tolerance attitude factor did not affect the students' learning outcomes with the help of google classroom. However, students who have a high and moderate tolerance attitude in the problem-based learning model class are better than students who have a high and moderate tolerance attitude in the active and conventional learning model class.Penelitian ini bertujuan untuk menganalisis: 1) perbedaan hasil belajar akidah akhlak berbantuan google classroom antara siswa yang belajar dengan model pembelajaran problem based learning dengan siswa yang belajar dengan model pembelajaran active learning dan konvensional 2) perbedaan hasil belajar akidah akhlak siswa berbantuan google classroom ditinjau dari sikap toleransi siswa; 3) pengaruh interaksi antara model pembelajaran dan sikap toleransi terhadap hasil belajar akidah akhlak siswa berbantuan google classroom. Penelitian ini merupakan penelitian kuantitatif dengan metode deskriptif. Teknik pengumpulan data yang digunakan yaitu tes hasil belajar akidah akhlak melalui google classroom dan angket sikap toleransi siswa menggunakan skala likert. Analisis data dalam penelitian ini menggunakan uji statistik non-parametrik, yaitu uji median. Hasil penelitian menunjukkan bahwa; 1) terdapat perbedaan hasil belajar akidah akhlak berbantuan google classroom yang signifikan antara siswa yang belajarnya dengan model pembelajaran problem based learning dengan siswa yang belajarnya dengan model pembelajaran active learning dan konvensional; 2) terdapat perbedaan hasil belajar akidah akhlak berbantuan google classroom yang signifikan antara siswa yang sikap toleransi kategori tinggi dengan siswa yang sikap toleransi kategori sedang, ini menunjukan bahwa sikap toleransi memiliki pengaruh terhadap hasil belajar akidah akhlak siswa yaitu semakin tinggi sikap toleransi siswa maka hasil belajar akidah akhlak pun akan meningkat, begitu juga sebaliknya; 3) faktor model pembelajaran dan faktor sikap toleransi tidak memberikan pengaruh terhadap hasil belajar akidah akhlak siswa berbantuan google classroom. Akan tetapi siswa yang memilki sikap toleransi kategori tinggi dan sedang di kelas model pembelajaran problem based learning lebih baik dibandingkan dengan siswa yang memiliki sikap toleransi kategori tinggi dan sedang di kelas model pembelajaran active learning dan konvensional.